A REVIEW ON THERAPEUTIC POTENTIAL OF HETEROCYCLIC PYRIMIDINE DERIVATIVES AS POTENT ANTIVIRAL AGENTS - EG, SAGMA; LAKSHMANAN, BASKAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Pyrimidine nucleus exhibited remarkable pharmacological activities. The review of an article indicates that the compounds having pyrimidine nucleus have a wide range of therapeutic uses that include antiviral, anti-inflammatory, antibacterial, anticancer, antiviral, anti-HIV, antihypertensive, sedatives and hypnotics, anticonvulsant, and antihistaminic. This review article is intended to describe the antiviral activity of a compound containing the pyrimidine nucleus. The chemistry of pyrimidine is a thriving field for the study of their pharmacological uses. Numerous methods for the synthesis of pyrimidine as also their diverse reactions offer enormous scope in the field of medicinal chemistry. The review article aims to reveal the work reported on the antiviral synthetic pyrimidine compound and the chemistry and biological activities of pyrimidine during the past few decades. During this review article, we are mainly focusing the viral activities in different derivatives of pyrimidine nucleus. Therefore, we are going to discuss some important issues such as the good ideas to resist our increasing viral disease and the importance of a pyrimidine nucleus in the viral drugs. Hence, these are the main things we are going to discuss in this article.